The olfactory bulb theta rhythm follows all frequencies of diaphragmatic respiration in the freely behaving rat - Rojas-Líbano, Daniel; Frederick, Donald E.; Egaña, José I.; Kay, Leslie M. (Frontiers in Behavioral Neuroscience, 2014)
Sensory-motor relationships are part of the normal operation of sensory systems. Sensing occurs in the context of active sensor movement, which in turn influences sensory processing. We address such a process in the rat olfactory system. Through recordings of the diaphragm electromyogram (EMG), we monitored the motor output of the respiratory circuit involved in sniffing behavior, simultaneously with the local field potential (LFP) of the olfactory bulb (OB) in rats moving freely in a familiar environment, where they display a wide range of respiratory frequencies. We show that the OB LFP represents the sniff cycle with high reliability at every sniff frequency and can therefore be used to study the neural representation of motor drive in a sensory cortex.